Penilaian Kualitas Air Sungai Kapuas dan Risiko Kesehatan Masyarakat yang Terkait dengan Praktik Higiene dan Sanitasi Masyarakat - Wahyudi, Reza; M. Fauzi, Anis; Budiarti, Sri; Pertiwi, Setyo; Sintawardhani, Neni (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
The Kapuas River is the main source of water for the community in Sanggau Regency, West Kalimantan; however, increasing anthropogenic pressure has raised concerns about water quality and public health risks. This study integrated the Exceedance Ratio (ER), Pollution Index (PI), and Quantitative Microbiological Risk Assessment (QMRA) to evaluate surface water quality from 2021to 2023 at four monitoring locations. Based on Class I standards, parameters that did not meet standards included iron (Fe) (ER = 4.00; 82% exceeded the limit), COD (ER = 2.37; 91%), BOD (ER = 2.10; 81%), and fecal coliforms (ER = 2.50; 82%). The PI values ranged from 2.16 to 5.07, classifying the rivers as lightly to moderately polluted, with a significant increase in 2023 (mean PI = 3.75 ± 0.82; p = 0.015). Although the Class II standards were nearly met, the QMRA indicated that the annual infection risk exceeded the WHO threshold (10⁻⁴ per person per year) at all locations. The exceedance factor (EF) in 2021–2022 ranged from 2.9–4.5 (adults) and 7.7–12 (children), increasing sharply in 2023 to 120 (adults) and 310 (children) at the water quality monitoring sites. These findings reveal a critical gap between regulation and health, highlighting the urgent need to strengthen sanitation management and health-based monitoring to support sustainable river governance and achieve Sustainable Development Goal (SDG) 6.